Effect of Dietary Fat Supplementation on Rumen Ecology in Goats - Ningal, Niel L. (Effect of Dietary Fat Supplementation on Rumen Ecology in Goats, 2024)
Altering the rumen ecosystem by supplementing fats to improve animal production is a significant scientific challenge that could bring remarkable effects on animal health, farm management, and animal productivity. Thus, the study was conducted to focus on the utilization of virgin coconut oil (VCO) and lard at different levels on goat fed concentrate on voluntary feed intake, rumen conditions, apparent nutrient digestibility and sequential degradation of Napier grass and concentrates. Three female rumen-cannulated goats were housed individually on elevated metabolism stalls with customized fecal and urine collection tools in five treatments on a crossover trial conducted over time following the Completely Randomized Design (CRD). Different inclusion rates of dietary fats of either VCO or Lard up to 5% inclusion rate did not affect voluntary feed intake of goat but lard supplementation at 5% inclusion rate increases purine derivative estimates. However, dietary fat supplementation did not influence the total VFA production, rumen NH3-N, pH, temperature, and apparent nutrient digestibility. There was an inverse association between rumen pH and NH3-N of goats. Nutrient apparent digestibility parameters such as CP and neutral detergent fiber (NDF) and acid detergent fiber (ADF) have a strong positive association. The relationship between the rest of the rumen condition parameters and apparent dry matter digestibility (DMD) showed no significant differences. Increased amount of VCO increases the CP degradability of Napier grass after 3 hours of incubation. The 3% of VCO supplementation decreases the NDF degradability after 48 hours of incubation. While VCO at 5% and lard of 3% decreases the ADF degradability. Despite the decreasing amount of detergent fiber degradability, the amount was still adequate for animal body requirement. Percentage degradability (% loss) of the nutrient content of concentrate was noticed exponentially in the first twelve hours of incubation and slowed down in the next few hours until 48 hours. Rumen microorganisms utilized efficiently the concentrate; effective degradability was recorded at 4.5 hr of ADF. Nutrient contents of the concentrates were degraded rapidly and/or components were soluble, or fine enough to escape from the bags. Thus, forages with low NDF have higher intakes than those with high NDF.